KAJIAN DAMPAK PEMEKARAN WILAYAH TERHADAP KESENJANGAN EKONOMI ANTAR DAERAH PESISIR DI PROVINSI BENGKULU - Arianti, Nyanyu Neti; Cahyadinata, Indra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
This research were conducted to analyze the impact of regional division to the economic disparity among the coastal regions in Bengkulu Province. The data used in this research were time series data of GRDP and population for the period of 1993 to 2000 (before division) and 2004 to 2011 (after divison) obtained from Statistic Office. The result of this research showed that the value of Index Williamson(IW) before regional division was 0,22 lower than the IW value after the regional division (0,43). That was meaned that after the regional division, economic disparity of the coastal region in Bengkulu Province higher than before the regional division.